Efficacy of Four Insecticides Applied to Fortified Rice with Basil against Major Stored-Product Insect Species - Paraskevi Agrafioti; Mariastela Vrontaki; Evagelia Lampiri; Christos I. Rumbos; Christos G. Athanassiou (Agronomy, 2023)
Rice is one of the most important foods since it is grown in many countries and consumed by the majority of the population. Ensuring food security through the protection of stored-product commodities has become one of the most important priorities worldwide. In this study, the effects of three insecticidal formulations and an available diatomaceous earth formulation on basil-fortified rice against the major stored-product insects were evaluated. The label dose of each insecticidal formulation was used. Insect mortality was determined after 1, 3, 7, 14 and 21 days for each species. The entire experiment was repeated three times by preparing different lots of treated and untreated rice for each treatment. The results of the diatomaceous earth treatments showed that the most susceptible individuals were Sitophilus oryzae adults and Oryzaephilus surinamensis larvae, while the least susceptible individuals were Rhyzopertha dominica and Tribolium castaneum adults. The tested insecticides were effective against S. oryzae, as mortality was 100%. Between the two pyrethroids, deltamethrin was more effective than cypermethrin in the tested insecticides. Our findings indicate that there are available insecticides on the market which can be obtained successfully for the durable protection of agricultural commodities after the harvest stage.